Pengaruh Kualitas Pelayanan, Persepsi Harga, dan Word Of Mouth Terhadap Keputusan Pembelian - Muhammad pascal fahreza; Sinthon Siahaan (Panorama Nusantara, 2022)
The purpose of this study was to determine and analyze the impact of quality of service, price perception, and word-of-mouth (WOM) on Estilo Coffee product purchase decisions. The population of this survey is Estilo coffee consumers from April to June 2022. The sampling method used non-probability-based sampling with a targeted sampling method to identify 100 respondents. Random procedure data collection using validation and reliability tested questionnaires. The analytical method used the classic test before the SPSS 20 multiple regression. 100 respondents as a tool, followed by F, T, classical assumptions, correlation and determination tests. The results of this survey show that quality of service variables have a significant impact on purchase decisions, price recognition variables have a significant impact on purchase decisions, and word-of-mouth (WOM) variables have a significant impact on customer purchase decisions. Therefore, variables such as quality of service, price recognition, and word-of-mouth (WOM) influence purchase decisions at the same time